Maps and metrics of insecticide-treated net access, use, and nets-per-capita in Africa from 2000-2020 - Amelia Bertozzi-Villa (Nature Portfolio, 2021)
Insecticide treated nets (ITNs) are an important part of malaria control in Africa and WHO targets aim for 80% coverage. This study estimates the spatio-temporal access and use of ITNs in Africa from 2000-2020, and shows that both metrics have improved over time but access remains below WHO targets.